Callus induction with 6-BAP and IBA as a way to preserve Prunus ledebouriana (Rosaceae), and endemic plant of Altai and Tarbagatai, East Kazakhstan (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Orazov A, Myrzagaliyeva A, Mukhitdinov N, Tustubayeva S. 2022. Callus induction with 6-BAP and IBA as a way to preserve Prunus ledebouriana (Rosaceae), and endemic plant of Altai and Tarbagatai, East Kazakhstan. Biodiversitas 23: 3178-3184. This article presents the results of the study of in vitro conditions for the cultivation and induction of callus tissues of a rare plant species Prunus ledebouriana(Schlecht.) Y.Y.Yao (Ledebour's almond), endemic plant to East Kazakhstan. For the first time, protocol and optimal composition of Murashige & Skoog (MS) were developed for obtaining calendemiclus tissues. The main indicator of successful introduction was the frequency of callus tissue formation in vitro. Two types of explants were used: the whole embryos and embryos with a removed root part. The removal of the root part inhibited the organogenesis of the embryonic root and the first shoot, which allowed the accumulation of nutrients for the growth of the callus mass and increased the frequency by 7.79±0.46%. Various exogenous phytohormones such as Kinetin, 6-BAP, GA, IBA were added to the MS culture medium. A decrease in Kinetin concentrations of 0.04 mg/L resulted in a lower intensity, but a higher frequency of formation (72.00±5.66%) and mass gain. The average concentration up to 0.5 mg/L of exogenous phytoregulators, such as GA and 6-BAP, resulted in frequency from 65.38±5.44% to 72.00±5.66%, the concentration of IBA up to 1 mg/L increased the frequency from 46.00±2.83 to 72.00±5.66%. The protocol for obtaining callus from an embryonic explant and the composition of the optimal nutrient medium for the induction of callusogenesis made it possible to obtain P. ledebouriana meristem tissues for further use in the development of callus cryopreservation technology.
Keywords: Prunus ledebouriana (Schlecht.) Y.Y.Yao, endemic species, rare species, callusogenesis, in vitro.